Avaliação da qualidade ambiental das praias da ilha de Itaparica, Baía de Todos os Santos, Bahia / Environmental quality of the beaches of the island of Itaparica, Todos os Santos Bay, Bahia - Jacqueline Lopes de Souza; Iracema Reimão Silva (Sociedade & Natureza)
The environmental quality of a beach represents one of the main factors for its attractiveness for recreational purposes. The present study had the main objective of evaluating the environmental quality of some of the most frequented beaches in the island of Itaparica, based on analyses of their balneability, sand quality and occurrence of marine litter. The Thermotolerant and Total Coliforms analyses during both periods characterized the beaches of Ponta de Itaparica, Ponta de Areia, Mar Grande andConceiçãoas adequate for primary contact recreation, while the Barra Grande beach was only considered adequate during the low season. When considering the analysis of these parameters for the sand, all beaches during the high season were adequate for primary contact activities, however, during the low season, only Barra Grande beach obtained a satisfactory result. A large amount of litter was found in the beaches sampled, particularly during the high season. Among the residues, plastic items predominated. The results indicate that the deficiency in the environmental sanitation infrastructure and disorderly use of the coast are the main responsible factors for the compromised environmental quality of the beaches of the island of Itaparica.